(untitled) (Research, Society and Development, 2022)
Breeding purebred dogs presents numerous challenges requiring the implementation of actions to ensure reproductive success. The aim of this study was to describe, through quantitative parameters, the relationship between birth weight (PN), weight gain (GPD) and inbreeding coefficient (CoI) with mortality observed in the neonatal period in the Australian Cattle Dog breed. A prospective, longitudinal study was carried out in a kennel registered to CBKC/FCI in the year 2020. Puppies had their vitality evaluated and were weighed daily until 45 days, with the heterogeneity of PN, GPD and CoI analyzed for each litter. Quartiles for the variables: PN, GPD and CoI were calculated and generalized linear models fitted using the R® system, with neonatal mortality as the binary outcome variable. Pup sex and primiparous occurrence were introduced as random effects. Multicollinearity was estimated between the predictors using Cramer’s method and the median area under the receiver operating characteristic curve (AUROC). The mean number of pups per litter was 5.88±1.93, mean BW was 258.98±47.19g. The highest odds ratio for mortality is found in the intermediate quartiles, and the fact that the mother is primiparous (p0.0014). The relationship between mortality in the neonatal period and primiparous mothers (AUROC≥0.7) was validated in the population studied.